THE PREDICTION POTENTIAL AREAS of CATCHING CAKALANG (Katsuwonus pelamis) BASED on CHLOROPHYLL-a DISTRIBUTION USING SATELLITE IMAGE NPP VIIRS IN WEST SUMATRA WATERS - Nur Audina; Usman '; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this studywas to determine the potential area for catchingcakalang (Katsuwonuspelamis) based on the distribution of chlorophyll-a satellite image of the NPP VIIRS in West Sumatra Waters by 2013. The methods used in this study are a survey method and spatial analysis. The results of this studysuggest that the location of the fishing ground cakalang by 2013 is at position 00 25 ' 48 " N – 50 34 ' 48" S and 950 25 ' 23 " E-1000 57 ' E. Distribution of chlorophyll-a who analyzed satellite images of NPP VIIRS between 0.13-0.26 mg/m3 whereas maximum CPUE as much as 0,1875 kg/trip in April. Correlation between chlorophyll-a and CPUE have strong relationship i.e. 0.60 while the influence of these variables both 36% among other factors. The resulting regression equation both of these variables showed that the increasing chlorophyll-a caused the decline of the CPUE.Keywords: Chlorophyll-A, Satelite Imagery, NPP VIIRS ,Katsuwonus pelamis